Sacrificing right to reputation in favour of freedom of speech in the context of defamation laws - Vorobiev, Nikita (Riga Graduate School of Law, 2017)
The right to reputation and right to the freedom of speech are two essential elements that play the role of a cornerstone of any modern democratic society, but bringing these two crucial pillars into the right balance is a real uphill struggle and often can be an unachievable goal. Even though it is difficult to strike the balance, it is still of a paramount importance to reduce the gap to the minimum between these two rights. This Thesis paper will set as its aim to discuss the law of defamation that is available under the UK law, in particular the recent trend, in author’s opinion, that is sacrificing the right to reputation in favour of freedom of speech, which became more prominent with the introduction of the Defamation Act 2013.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; United Kingdom; Freedom of speech; Right to reputation